2004
DOI: 10.1109/tmi.2004.826051
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Depth Position in 2-D/3-D Registration of Knee Implants Using Single-Plane Fluoroscopy

Abstract: Two-dimensional (2-D)/three-dimensional (3-D) registration techniques using single-plane fluoroscopy are highly important for analyzing 3-D kinematics in applications such as total knee arthroplasty (TKA) implants. The accuracy of single-plane fluoroscopy-based techniques in the determination of translation perpendicular to the image plane (depth position), however, is relatively poor because a change in the depth position causes only small changes in the 2-D silhouette. Accuracies achieved in depth position u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
133
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 165 publications
(134 citation statements)
references
References 19 publications
0
133
0
Order By: Relevance
“…19 The current study was the first experimental validation of a 3D fluoroscopy method dedicated to the in vivo measurement of mandibular motion under real-life conditions. This was in contrast to previous validation studies of 3D fluoroscopy on other joints, which either used ''clean'' images of the bone outside the body 27 or only assessed the accuracy of the measurement at static conditions. 28 The current study reported the means and standard deviations of the measurement errors.…”
Section: Figurementioning
confidence: 91%
“…19 The current study was the first experimental validation of a 3D fluoroscopy method dedicated to the in vivo measurement of mandibular motion under real-life conditions. This was in contrast to previous validation studies of 3D fluoroscopy on other joints, which either used ''clean'' images of the bone outside the body 27 or only assessed the accuracy of the measurement at static conditions. 28 The current study reported the means and standard deviations of the measurement errors.…”
Section: Figurementioning
confidence: 91%
“…Zuffi et al [8] and Yamazaki et al [7] use an Iterative Closest Point (ICP) algorithm to align the object's occluding contour with its observed X-ray silhouette. Since these methods are not robust against the presence of edge points generated by other objects (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…1(b) and 1(c)). Consequently, traditional 2D/3D registration algorithms [6,7,8] might converge towards a local optimum representing a pose symmetrical to the true one.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations